How to scale your small business : the 3 fundamental rules for a business to scale to profit (Apress, 2018)
"This video covers the 3 fundamental laws of scale, which must be answered in order for a business to scale to profit. You'll learn how to take a single-person, micro business and scale the reach and profitability of the business. If you're delivering the work to your customers, you can see that there is a limit to the amount of income you can generate. You can either work more hours, or you can increase your prices. You're probably already working every hour you can. And there is a limit to how much you can charge for your services. The solution is to scale out your delivery and examine the results you can provide to your audience. Your job becomes to deliver those results through as many scalable mediums as you can."--Resource description page